Prevalence and abundance of plant-parasitic nematodes in New Zealand maize fields: effects of territory, soil orders, crop stage, and sampling time - Thiruchchelvan, N.; Kularathna, M.; Moukarzel, R.; Casonato, S.; Condron, L.M. (Tylor and Francis, 2024)
Plant-parasitic nematodes (PPNs) are significant agricultural pests that can reduce maize yields. This study examines the prevalence, abundance, and diversity of PPNs in New Zealand maize fields, focusing on the effects of territory, soil orders, crop stages, and sampling times. Seven PPN genera were identified: Pratylenchus spp. (root-lesion), Helicotylenchus spp. (spiral), Meloidogyne spp. (root-knot), Heterodera spp. (cyst), Paratylenchus spp. (pin), Criconemella spp. (ring), and Tylenchus spp. PPNs were present in 98% of the samples, with Pratylenchus spp. being the most prevalent (91%), followed by Helicotylenchus spp. (38%). Compared to Waikato and Manawatu-Whanganui, Canterbury had the highest nematode populations, particularly of Pratylenchus spp. And Helicotylenchus spp. Brown and pallic soils supported higher PPN abundances. Sampling during the maize harvesting stage and late autumn resulted in the highest nematode populations and diversity indices. Pratylenchus spp. populations often exceeded the economic threshold of 500 Pratylenchus kg−1 of soil, suggesting a significant threat to maize yield in New Zealand. The findings highlight the need for further research to assess the impact of Pratylenchus spp. on maize yield and to develop effective management practices for maize cultivation in the country.
, M., Moukarzel, R., Casonato, S., & Condron, L. M.
Keywords: Plant-parasitic nematodes; Maize; Pratylenchus; Nematode diversity; Soil orders; Crop stage; Sampling time; Lesion nematodes; Spiral nematodes; New Zealand